Experimental study on cold start performance of PEMFC based on parallel flow channels. (1st January 2022) - Yue, Like; Wang, Shixue; Zhu, Yu; Fan, Yue
Abstract: In this study, experimental methods are used to study the effect of assembly torque and channel size on cold start performance. Through the analysis of pressure distribution, fuel cell voltage, cathode gas inlet and outlet pressure drop and high frequency impedance, it is considered that, under the experimental conditions of this study, the fuel cell assembly torque is 2 N m, which has better cold start performance than the assembly torque of 1 N m and 4 N m. In addition, Under the condition of 2 N m assembly torque, the effect of four different flow channel sizes on the pressure distribution and cold start performance of the fuel cell was studied. It is found that when the width of channel is 0.5 mm, the depth of channel is 0.3 mm, the cold start performance is best. Highlights: When the channel width is 0.5 mm, the pressure distribution is more uniform than that of 1.0 mm. When the assembly torque is 2 N m, the cold start performance of fuel cell is better. The channel width of 0.5 mm is easier to successfully cold start than 1.0 mm. The channel depth of 0.3 mm is more conducive to cold start than 1.0 mm.